WAYS TO STRENGTHEN FINANCIAL STABILITY AND RESOURCE BASE OF COMMERCIAL BANKS (ResearchJet Journal of Analysis and Inventions, 2021)
The article discusses the problems of financial stability and the formation of the resource base of commercial banks, the adequacy of bank capital, profitability indicators and the importance of increasing bank capital. It is important to increase the volume of long-term deposits, since the deposit base of commercial banks and its sufficiency are an indicator of the reliability of the banking system. The article also analyzes the key indicators characterizing the resource base of the bank and the financial stability of banks.